On the modeling of tensile behavior of ultra-high performance fiber-reinforced concrete with freezing-thawing actions. (1st October 2019) - Zhou, Zhidong; Xie, Ruifeng; Qiao, Pizhong; Lu, Linjun
Abstract: An analytical model is proposed to predict the tensile behavior of Ultra-High Performance fiber-reinforced Concrete (UHPC) with extended cyclic freezing-thawing (F-T) actions. Based on the work mechanisms of stress transfer at the matrix-fiber interface, the fiber pullout behavior is modeled, from which the combined effects of fiber orientation, fiber snubbing and matrix spalling on the tensile responses of UHPC are characterized with a fiber reinforcement efficiency function. The nanoindentation test results show that the interfacial transition zone (ITZ) between steel fiber and cementitious matrix deteriorates over the F-T period, and the thickness of this ITZ weak band gradually increases from 22 μm at 0 cycle to 60 μm at 1500 F-T cycles. A good agreement is achieved between the analytical and experimental tensile responses of UHPC at various F-T cycles, and the predictability of the model is improved by adjusting the coefficients that govern the softening branch of tensile stress-crack width curves. The proposed analytical model can be used to effectively predict the tensile behavior of UHPC and its degradation effect due to F-T actions.